2021
DOI: 10.1016/j.jvir.2021.06.025
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid Embolization for Nonsurgical Treatment of Nodular Goiter: A Single-Center Experience in 56 Consecutive Patients

Abstract: Purpose: To investigate the safety and efficacy of thyroid artery embolization (TAE) in the treatment of nodular goiter (NG).Methods: During a 5.5-year period, 56 consecutive patients with a NG underwent TAE. In Group A, there were 20 patients with a solitary/dominant 5-11-cm nodule, and in Group B, there were 36 patients with numerous nodules. Of the 56 patients, 47 (84%) had a retrosternal goiter and 25 had hyperthyroidism. In all patients, clinical and radiological evaluations were made at baseline and 6 mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 25 publications
1
8
1
Order By: Relevance
“…While pilot examinations could be helpful to compare the virtual examination with the in-person one, no pilot examination was conducted due to time constraints. Despite the benefit of the virtual examination, the candidates prefer the inperson experience, which is contrary to the findings reported by Chaurasia et al (1).…”
Section: Editorcontrasting
confidence: 89%
See 2 more Smart Citations
“…While pilot examinations could be helpful to compare the virtual examination with the in-person one, no pilot examination was conducted due to time constraints. Despite the benefit of the virtual examination, the candidates prefer the inperson experience, which is contrary to the findings reported by Chaurasia et al (1).…”
Section: Editorcontrasting
confidence: 89%
“…A recent study by Yilmaz et al (1) found that TAE is safe and effective for the management of NG. However, minor complications occurred in 44.6% (25/56) of the patients, and major complications occurred in 3.6% (2/56) of the patients.…”
Section: Editormentioning
confidence: 97%
See 1 more Smart Citation
“…Therefore, thyroidectomy remains the mainstay treatment for large, symptomatic multinodular goiters. However, if surgery is contraindicated or refused, a staged ablative approach or thyroid arterial embolization 22 could be considered in carefully selected patients as adjunctive locoregional therapy for symptom palliation. RFA can interfere with a pacemaker, implanted cardiac defibrillator, or cochlear implant, and the presence of such devices is a relative contraindication to RFA, although, in such cases, bipolar electrodes or alternative TA techniques may be used.…”
Section: Discussionmentioning
confidence: 99%
“…Yilmaz et al ( 5 ) successfully used transfemoral thyroid artery embolization (TAE) to treat large thyroid nodules with considerable volume reduction. Compared with transfemoral access (TFA), transradial access (TRA) is becoming more widely accepted for various neurointerventional diagnoses and therapy procedures ( 6 - 8 ).…”
Section: Introductionmentioning
confidence: 99%